Analisis Komponen Saluran Udara Tegangan Menengah (SUTM) 20 KV di Penyulang Merbau - Jambi - Rozlinda Dewi (Universitas Batanghari Jambi, 2020)
Distribution network planning is not loose from how the distribution system is built. From planning (the construction of the following components) to implementation in the field, determining the quality and reliability of the system can be fulfilled. This research analyzes about the implementation of medium-voltage air duct components (SUTM) 20 kV rework location Merbau in the area Ma. Tembesi Kab. Batanghari-Jambi, is in accordance with the standard used by PLN (S-PLN). One is how to determine the number of components used in a SUTM project. The research method used is the observation and measurement methods in the field. The observation method uses standardized standard theory according to the standard Book of State electricity General Company (S-PLN). The results concluded that the use of components in the field for the use of an AAAC cable conductor for 11,025 M is almost close to the standard, the difference only ranges from 7.2% (+). While the use of Poles although the same number of 70 BH covers a type of concrete pole 12 m 200 And as many as 69 BH, pole 9m 100 And 13 PCs, but there is a difference in the amount of the use of Poles 12m and 9m between the calculated and realization values The use of poles of certain lengths for project executor should reference the PLN standard even though the workload is still being fulfilled (200 And). With always being evaluated in each project, this data can be used as input for the project owner or executor, so that the quality and reliability of the system can be fulfilled